Training On Coping Strategies For English Speech Anxiety For Grade VI Students In Toket 1 Elementary School - Arifin, Samsul; Sa'i, Mad (SANISKALA : Jurnal Pengabdian Masyarakat, 2025)
English speaking anxiety is a common challenge faced by students, especially when it comes to public speaking. Factors such as lack of confidence, limited vocabulary, and fear of making mistakes often become barriers to communication. This study aims to identify and implement effective strategies in overcoming speaking anxiety. The method used in this study is strategy-based training involving questionnaires, vocal exercises, relaxation techniques, role-playing, and direct assistance by tutors. The training was conducted on grade VI students of SDN Toket 1 with a phased approach, starting from the identification of anxiety levels to speaking practice using prepared speech texts. The results showed that relaxation techniques, gradual practice, and motivation from tutors were able to increase students' confidence and reduce anxiety when speaking. With the proper application of the method, students can speak more fluently, confidently, and effectively in English.